Early weight gain predicts later metabolic syndrome in depressed patients treated with antidepressants: Findings from the METADAP cohort. (December 2018) - El Asmar, Khalil; Fève, Bruno; Colle, Romain; Trabado, Séverine; Verstuyft, Céline; Gressier, Florence; Vievard, Albane; Haffen, Emmanuel; Polosan, Mircea; Ferreri, Florian; Falissard, Bruno; Chanson, Philippe; et al.
Abstract: Background: Metabolic syndrome (MetS) is a major public health issue. We assessed whether early weight gain predicts later MetS in depressed patients treated with antidepressants. Methods: In the 6-month prospective METADAP cohort, 260 non-overweight patients with a Major Depressive Disorder (MDD) and a current Major Depressive Episode (MDE) were assessed for early weight gain (>5%) after one month of treatment, and for the later incidence of MetS after three and six months of treatment. Outcome variables were MetS, the number of MetS criteria, and each MetS criterion (high Waist Circumference (WC), high Blood Pressure (BP), high triglyceridemia (TG), low HDL-Cholesterolemia, and high Fasting Plasma Glucose (FPG). Multivariate models were adjusted for age, sex, previous MDD duration, severity of current MDE, and antidepressants. Results: 24.6% of patients had early weight gain. Compared to those without weight gain, patients with early weight gain had higher MetS incidence: 16.7% vs. 6.9% after 3 months (p = 0.07), and 23.8% vs. 7.1% after 6 months (p = 0.02). Among completers (n = 120), early weight gain was significantly associated with later MetS incidence (OR: 5.5) and a higher number of MetS criteria (IRR: 1.7). This effect was driven by the WC, TG, and HDL-C criteria. Conclusion: Compared to Non-early weight gainers, patients with early weight gain in the first month of antidepressant treatment have a significant higher risk of developing MetS during the 6 months of treatment. Early weight monitoring is recommended in order to set preventive measures to avoid new metabolic syndromes in depressed patients treated with antidepressants.